2017
DOI: 10.1155/2017/8539093
|View full text |Cite
|
Sign up to set email alerts
|

Phragmites australis+Typha latifoliaCommunity Enhanced the Enrichment of Nitrogen and Phosphorus in the Soil of Qin Lake Wetland

Abstract: Aquatic plants play an essential role and are effective in mitigating lake eutrophication by forming complex plant-soil system and retaining total nitrogen (TN) and phosphorus (TP) in soils to ultimately reduce their quantities in aquatic systems. Two main vegetation types (Phragmites australis community and P. australis + Typha latifolia community) of Qin Lake wetland were sampled in this study for the analysis of TN and TP contents and reserves in the wetland soils. The results showed that (1) the consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Based on the above, we found that NO 3 increased in AFIs and had no effect on PO 4 3-, as has been recorded in Phragmites, which is that it is capable of enriching the medium due to its input of N (Ge et al, 2017). But that does not coincide with other proven models where these nutrients are removed (Abed et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Based on the above, we found that NO 3 increased in AFIs and had no effect on PO 4 3-, as has been recorded in Phragmites, which is that it is capable of enriching the medium due to its input of N (Ge et al, 2017). But that does not coincide with other proven models where these nutrients are removed (Abed et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 59%
“…To a certain extent, the increase of plant biomass indicated that the N in different forms is assimilated and absorbed by wetland plants (Sun et al 2019, Zak et al 2014, and vegetation harvesting may simulate the overall N removal (Jabońska et al 2020), those processes also caused the decrease of TN content in water. Vegetation covering was essential to the enrichment of TN, indicating the importance of biologically related xation in wetland soil (Ge et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Plants offer an added bene t to wetland restoration and are effective in mitigating wetland eutrophication by absorbing, assimilating, and reutilizing nutrients such as nitrogen and phosphorus in the water body and sediment to support their own physiological processes and growth for the following year (Aerts and Chapin 1999, Deegan et al 2007, Gan et al 2011, Ge et al 2017, Ling and Li 2018, Rejmankova 2005). Wetland plants root share some common characteristics such as providing oxygen and secrete oxygen to form aerobic, facultative and anaerobic micro-environments around the rhizosphere, thereby promoting the degradation of pollutants in sewage by microbial nitri cation and denitri cation (Mic et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To a certain extent, the increase in plant biomass indicated that the N is assimilated and absorbed by wetland plants in different forms [37,38], and vegetation harvesting may simulate the overall N removal [39]; these processes also caused the decrease in TN content in water. Vegetation covering was essential to the enrichment of TN, indicating the importance of biologically related fixation in wetland soil [20].…”
Section: Discussionmentioning
confidence: 99%
“…Plants offer an added benefit to wetland restoration and are effective in mitigating wetland eutrophication by absorbing, assimilating, and reutilizing nutrients such as nitrogen and phosphorus in the water body and sediment to support their own physiological processes and growth for the following year [15][16][17][18][19][20]. Wetland plant roots share some common characteristics, such as providing oxygen and secreting oxygen to form aerobic, facultative and anaerobic micro-environments around the rhizosphere, thereby promoting the degradation of pollutants in sewage by microbial nitrification and denitrification [21].…”
Section: Introductionmentioning
confidence: 99%